THE ENVIRONMENTAL IMPACT AND THE WASTEWATER QUALITY OF THE TEXTILE WET PROCESSING IN THE SUDAN - , admin; Ahmed, Mutasim.A.; Haroon, Elfadil H. (Gezira Journal of Health Sciences, 2009)
The purpose of this study is to evaluate the environmental impacts of the textile wet processing in one Textile Mill (at Khartoum North) and to estimate the pollution load and the required degree of treatment of wastewater produced. The study includes the important parameters affecting pollution overload associated with the wet processing stages, such as desizing, scouring, bleaching, dyeing, finishing and washing. Different industrial wastewater samples were taken at different intervals of time, and subjected to various tests, by the different analytical methods. The instrumental methods of analysis used are UV- visible and atomic absorption spectrophotometer (AAS), digital pH meter, COD reactor, BOD incubator, etc. The study proved that, the extensive use of chemicals, dyestuffs and water results in generation of highly polluted water differing in magnitude and quality.    Key words: Textile, Wet Processing, Pollution, Wastewater, Environmental    Performance